Random projection RBF nets for multidimensional density estimation - Skubalska-Rafajłowicz, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
The dimensionality and the amount of data that need to be processed when intensive data streams are observed grow rapidly together with the development of sensors arrays, CCD and CMOS cameras and other devices. The aim of this paper is to propose an approach to dimensionality reduction as a first stage of training RBF nets. As a vehicle for presenting the ideas, the problem of estimating multivariate probability densities is chosen.
Keywords: radial basis functions; multivariate density estimation; dimension reduction; normal random projection; novelty detection